Comparison on Difference in Conventional Electronic Device and IoT (Internet of Things) Enabled Sensors Readings of Vital Signs in Patients - Anjali, Yeole; D.R, Kalbande (International Journal of Engineering and Technology, 2018)
Â The comparative study was carried out on difference in reading of conventional bedside monitor and IoT (Internet of Things) enabled sensors recordings of vital signs like temperature, heart rate and spo2 in patients of PKC hospital, Vashi. The study was conducted on selected 10 patients. For each subject conventional device and IoT sensors readings of temperature, heart rate and spo2 were recorded for 5 minutes for 3 days. Readings from conventional devices and IoT sensors were recorded simultaneously. Data included readings of temperature, Spo2 and heart rate. Total samples collected are minimum 324 and maximum 330.Clinically approved results are present in the paper. The recordings were compared to know difference between conventional device readings and IoT enabled sensors reading. The study findings discovered that there is no momentous difference between the conventional device readings and IoT based sensors readings.Â